The EFFECT OF SCALE CATEGORY NUMBER ON ACCURACY OF PREDICTIVE VALIDITY OF MATHEMATICAL SELF-EFFICACY SCALE - Iwan Setiadi; Erdawaty Kamaruddin; Soeprijanto (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
The purpose of this study was to obtain empirical data about the effect of the number of scale categories on the accuracy of the predictive validity of the Mathematics Self-Efficacy Scale between those using a scale of three categories of answers and a scale of five categories of answers. This research uses a quantitative method of comparative study. The population in this study were all students of Madrasah Aliyah (Islamic High School) class XI IPA in North Jakarta in the academic year 2019/2020. Sampling was done by simple random sampling and there were 230 students from six public and private Madrasah Aliyah. The instruments used were tests and non-tests. The test instrument was in the form of a Mathematics learning achievement test and a non-test instrument in the form of a Mathematics Self-Efficacy Scale. The research hypothesis was tested using a t-test. The results showed that the average standard error of estimating the predictive validity of the Mathematics Self-Efficacy Scale using the five answer categories scale was lower than the scale of the three answer categories. The conclusion of the study is the predictive validity of the Mathematics Self-Efficacy Scale which uses a five-answer category scale that is more accurate in predicting mathematics learning outcomes.